2011
DOI: 10.1017/s0266467410000787
|View full text |Cite
|
Sign up to set email alerts
|

Solute behaviour and export rates in neotropical montane catchments under different land-uses

Abstract: Abstract:To improve our knowledge of the influence of land-use on solute behaviour and export rates in neotropical montane catchments we investigated total organic carbon (TOC), Ca, Mg, Na, K, NO 3 and SO 4 concentrations during April 2007-May 2008 at different flow conditions and over time in six forested and pasture-dominated headwaters (0.7-76 km 2 ) in Ecuador. NO 3 and SO 4 concentrations decreased during the study period, with a continual decrease in NO 3 and an abrupt decrease in February 2008 for SO 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 58 publications
(161 reference statements)
1
19
0
Order By: Relevance
“…Studies on both scales identify the similar hydrological processes as being active within the study area. Studies on the micro-scale (Boy et al, 2008;Goller et al, 2005), supported by solute data and end member mixing analysis at the meso-scale (Bücker et al, 2011;Crespo et al, 2012), showed that fast "organic horizon flow" in forested catchments dominates during discharge events if the mineral soils are water saturated prior to the rainfall. Due to an abrupt change in saturated hydraulic conductivity (K sat ) between the organic (38.9 m d −1 ) and the near-surface mineral layer (0.15 m d −1 ), this organic horizon flow can contribute up to 78 % of the total discharge during storm events (Fleischbein et al, 2006;Goller et al, 2005).…”
Section: Current Process Understanding At the Catchment Scalementioning
confidence: 98%
See 2 more Smart Citations
“…Studies on both scales identify the similar hydrological processes as being active within the study area. Studies on the micro-scale (Boy et al, 2008;Goller et al, 2005), supported by solute data and end member mixing analysis at the meso-scale (Bücker et al, 2011;Crespo et al, 2012), showed that fast "organic horizon flow" in forested catchments dominates during discharge events if the mineral soils are water saturated prior to the rainfall. Due to an abrupt change in saturated hydraulic conductivity (K sat ) between the organic (38.9 m d −1 ) and the near-surface mineral layer (0.15 m d −1 ), this organic horizon flow can contribute up to 78 % of the total discharge during storm events (Fleischbein et al, 2006;Goller et al, 2005).…”
Section: Current Process Understanding At the Catchment Scalementioning
confidence: 98%
“…This study is conducted in a 75 km 2 montane rain forest catchment in south Ecuador, the upper part of the Rio San Francisco, which has been under investigation since 2007 (Bogner et al, 2014;Boy et al, 2008;Bücker et al, 2011;Crespo et al, 2012;Fleischbein et al, 2006;Goller et al, 2005;Timbe et al, 2014;Windhorst et al, 2013b). The findings of those studies (briefly synthesized in Sect.…”
Section: Windhorst Et Al: Stable Water Isotope Tracing Through Hymentioning
confidence: 99%
See 1 more Smart Citation
“…Export of all base cations (Na + , Mg 2+ , K + , and Ca 2+ ), NO 3 − and Cl − was lower from both soybean and forest watersheds than from other watersheds in the lowland Amazon, montane Ecuador, or Puerto Rico (McDowell and Asbury 1994, Williams and Melack 1997, Bücker et al 2011. Export of all base cations (Na + , Mg 2+ , K + , and Ca 2+ ), NO 3 − and Cl − was lower from both soybean and forest watersheds than from other watersheds in the lowland Amazon, montane Ecuador, or Puerto Rico (McDowell and Asbury 1994, Williams and Melack 1997, Bücker et al 2011.…”
Section: Increased Discharge Increases Annual Solute Yield From Soybementioning
confidence: 99%
“…However, concentrations were higher than values reported for streams in the Luquillo Experimental Forest, Puerto Rico, where Tabonuco (Dacryodes excelsa) and Colorado (Cyrilla racemiflora) forest types dominate (McDowell and Asbury, 1994) and in evergreen and rain forest areas in Costa Rica (Newbold et al, 1995). Values were similar to nitrate concentrations in streams draining mountain catchments covered by evergreen seasonal forest in northern Venezuela (Castillo, 2010) and in catchments in Ecuador where cloud forest is the dominant vegetation (Bücker et al, 2011). At some sites like San Nicolás and Vista Hermosa 1, nitrate and phosphorus concentrations were severalfold higher than at the rest of the streams.…”
Section: Figure 4 Principal Component Analyses (Pca) Based On Stream mentioning
confidence: 55%